Scooby-Doo! World of Mystery 51 England - Cheddar Gorge - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
Yikes!The gang visit some creepy caves where Shaggy and Scooby's Snacking is interrupted by a scary visitor...
Keywords: Juvenile literature-Fiction